Generation of insulin-producing cells from human induced pluripotent stem cells on PLLA/PVA nanofiber scaffold. (31st October 2018) - Enderami, Seyed Ehsan; Kehtari, Mousa; Abazari, Mohammad Foad; Ghoraeian, Pegah; Nouri Aleagha, Maryam; Soleimanifar, Fatemeh; Soleimani, Masoud; Mortazavi, Yousef; Nadri, Samad; Mostafavi, Hossein; Askari, Hassan
Abstract: Pancreatic tissue engineering as a therapeutic option for restoring and maintenance of damaged pancreas function has a special focus to using synthetic Scaffolds. This study was designed to evaluate pancreatic differentiation of human induced pluripotent stem cells (hiPSCs) on poly-L-lactic acid and polyvinyl alcohol (PLLA/PVA) scaffolds as 3 D matrix. During differentiation process, morphology of cells gradually changed and iPSCs derived insulin producing cells (iPSCs-IPCs) formed spherical shaped cell aggregation that was the typical shape of islets of pancreas. The highly efficient differentiation of iPSCs into a relatively homogeneous population of IPCs was shown by immunostaining. Real-time reverse transcription polymerase chain reaction (RT-PCR) results demonstrated that iPSCs-IPCs expressed pancreas-specific transcription factors (Pdx1, insulin, glucagon and Ngn3). The expressions of these transcription factors in PLLA/PVA scaffold were significantly higher than 2 D groups. Furthermore, we showed that concentration of insulin and C-peptide in PLLA/PVA scaffold and/or 2 D culture in response to various concentrations of glucose increased but the difference between them were not significant. Altogether the current results demonstrated that PLLA/PVA scaffold could provide the microenvironment that promotes the pancreatic differentiation of iPSCs, up-regulate pancreatic-specific transcription factors and improved metabolic activity.